Composition and temporal patterns of larval fish communities in Chesapeake and Delaware Bays - Filipe Ribeiro; Edward Hale; Edward Hale; Eric Hilton; Todd Clardy; Alison Deary (Frontiers in Marine Science, 2015)
Comparing larval fish assemblages in different estuaries provides insights about the coastal distribution of larval populations, larval transport, and adult spawning locations (Ribeiro et al. 2015). We simultaneously compared the larval fish assemblages entering two Middle Atlantic Bight (MAB) estuaries (Delaware Bay and Chesapeake Bay, USA) through weekly sampling from 2007 to 2009. In total, 43 taxa (32 families) and 36 taxa (24 families) were collected in Delaware and Chesapeake Bays, respectively. Mean taxonomic diversity, mean richness, and evenness were generally lower in Delaware Bay. Communities of both bays were dominated by Anchoa spp., Gobiosoma spp., Micropogonias undulatus, and Brevoortia tyrannus; Paralichthys spp. was more abundant in Delaware Bay and Microgobius thalassinus was more abundant in Chesapeake Bay. Inter-annual variation in the larval fish communities was low at both sites, with a relatively consistent composition across years, but strong seasonal (intra-annual) variation in species composition occurred in both bays. Two groups were identified in Chesapeake Bay: a ‘winter’ group dominated by shelf-spawned species (e.g. M. undulatus) and a ‘summer’ group comprising obligate estuarine species and coastal species (e.g. Gobiosoma spp. and Cynoscion regalis, respectively). In Delaware Bay, 4 groups were identified: a ‘summer’ group of mainly obligate estuarine fishes (e.g. Menidia sp.) being replaced by a ‘fall’ group (e.g. Ctenogobius boleosoma and Gobionellus oceanicus); ‘winter’ and ‘spring’ groups were dominated by shelf-spawned (e.g. M. undulatus and Paralichthys spp.) and obligate estuarine species (e.g. Leiostomus xanthurus and Pseudopleuronectes americanus), respectively. This study demonstrates that inexpensive and simultaneous sampling in different estuaries provides important insights into the variability in community structure of fish assemblages at large spatial scales.